Method for manufacturing an electrode for an electrochemical device, method for manufacturing an electrochemical device, and forming material for an electrode

JP7632278B2Active Publication Date: 2025-02-19ZEON CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021512069
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2020-03-27
Publication Date
2025-02-19
Estimated Expiration
2040-03-27

AI Technical Summary

Benefits of technology

【0018】 本発明によれば、製造装置の腐食および臭気の問題が生じ難い電気化学デバイス用電極の製造方法、および、当該製造方法で製造した電極を用いた電気化学デバイスの製造方法を提供することができる。 また、本発明によれば、電極の製造に用いた際に製造装置の腐食および臭気の問題の発生を抑制し得る電極用成形材料を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632278000001
    Figure 0007632278000001
  • Figure 0007632278000002
    Figure 0007632278000002
Patent Text Reader

Abstract

The present invention provides a method for producing an electrode for electrochemical devices, which is not likely to cause a problem of corrosion and odor of a production apparatus. A method for producing an electrode for electrochemical devices according to the present invention comprises a step wherein an electrode that has a composite layer having a porosity of 10% by volume or less is formed using a molding material for electrodes containing an active material and an ion conductor having an ionic conductivity of 10-4 S / cm or less at the temperature of 5°C; the ion conductor contains a low-molecular-weight organic compound having a molecular weight of less than 10,000; and the low-molecular-weight organic compound comprises a compound having a volatility that is not less than the volatility of N-methyl pyrrolidone at a proportion of from 0% by mass to 20% by mass (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an electrode for an electrochemical device, a method for producing an electrochemical device, and a molding material for an electrode. [Background technology]

[0002] Electrodes containing an active material have been used in electrochemical devices such as primary batteries, such as lithium primary batteries; nonaqueous secondary batteries, such as lithium ion secondary batteries, lithium metal secondary batteries, sodium ion secondary batteries, potassium ion secondary batteries, magnesium secondary batteries, and aluminum secondary batteries; solar cells, such as dye-sensitized solar cells; capacitors, such as electric double layer capacitors and lithium ion capacitors; electrochromic display devices; electrochemical light-emitting elements; electric double layer transistors; and electrochemical actuators.

[0003] For example, in Patent Document 1, a screw extruder is used to manufacture a positive electrode for an alkali metal polymer battery in which an ion-conductive polymer electrolyte material such as polyethylene oxide, a cathode active material such as vanadium oxide, a conductive filler such as carbon and graphite particles, a lithium salt, and a plasticizer are mixed and extruded onto a metal foil to form a positive electrode film on the metal foil.

[0004] Also, for example, in Patent Document 2, a viscous solution containing polyethylene oxide, carbon, LiV3O8, ethylene carbonate, propylene carbonate, PVdF-HFP copolymer (a copolymer of polyvinylidene fluoride and hexafluoropropylene), and acrylonitrile is applied to an aluminum foil, and then the acrylonitrile is evaporated to produce a positive electrode for a lithium battery in which an electrode film is provided on the aluminum foil. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2005-519442 [Patent Document 2] Special Publication No. 2006-522441 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the technology described in Patent Document 1 has a problem in that the metal parts of the manufacturing equipment are corroded because the raw material for the positive electrode film contains lithium salt.

[0007] Furthermore, the technique described in Patent Document 2 has a problem in that a large amount of a volatile solvent such as acrylonitrile is volatilized when forming the electrode film, which can cause problems such as odor.

[0008] Therefore, an object of the present invention is to provide a method for manufacturing electrodes for electrochemical devices which is less likely to cause problems of corrosion of the manufacturing equipment and odor generation, and a method for manufacturing electrochemical devices which use electrodes manufactured by this method. Another object of the present invention is to provide an electrode molding material which, when used in the manufacture of electrodes, can suppress the occurrence of problems such as corrosion of manufacturing equipment and odor generation. [Means for solving the problem]

[0009] As a result of intensive research to achieve the above-mentioned object, the present inventors have found that by using an electrode molding material containing a specified ion conductor, it is possible to manufacture electrodes while suppressing the occurrence of problems such as corrosion of the manufacturing equipment and odor generation, and have completed the present invention.

[0010] That is, the present invention has an object to advantageously solve the above-mentioned problems, and a method for producing an electrode for an electrochemical device according to the present invention comprises: -4The method includes forming an electrode having a composite layer with a porosity of 10% by volume or less using an electrode forming material containing an ion conductor having an ion conductivity of 0.01% or less and an ion conductor having an ion conductivity of 0.01% or less. The ion conductor contains a low molecular weight organic compound having a molecular weight of less than 10,000, and the low molecular weight organic compound contains a compound having a volatility rate equal to or higher than that of N-methylpyrrolidone in a ratio of 0% by mass to 20% by mass. In this way, by manufacturing an electrode using an electrode forming material containing an ion conductor having an ion conductivity of the upper limit or less, corrosion of the manufacturing equipment can be suppressed. In addition, if the ratio of the compound having a volatility rate equal to or higher than that of N-methylpyrrolidone in the low molecular weight organic compound is 20% by mass or less, odor problems during manufacturing can be suppressed. In the present invention, "ionic conductivity" refers to ionic conductivity measured by an alternating current method, and can be obtained by taking the reciprocal of the volume resistivity calculated from the arc diameter of the Nyquist plot obtained by applying an alternating current in the range of 10 to 100 mV to a sample sandwiched between two parallel stainless steel plates in a thermostatic chamber controlled to a measurement temperature of ±1°C. In addition, the "volatility" can be measured at a temperature of 18°C ​​by the method described in the Reference Example. Furthermore, the "porosity" can be obtained by calculating the rate at which the actual specific gravity deviates from the theoretical specific gravity (= {(theoretical specific gravity - actual specific gravity) / theoretical specific gravity} × 100%) at a temperature of 25°C.

[0011] In the method for producing an electrode for an electrochemical device of the present invention, the ion conductor is preferably a viscous composition containing a polymer in a proportion of 50% by mass or less. If the content of the polymer in the ion conductor is 50% by mass or less, the electrode forming material can be easily prepared and the content of the active material can be easily increased.

[0012] In the method for producing an electrode for an electrochemical device of the present invention, the ion conductor preferably does not contain an ionic substance. If the ion conductor does not contain an ionic substance, corrosion of the production equipment can be further suppressed.

[0013] In the method for producing an electrode for electrochemical devices of the present invention, the step preferably includes forming the composite layer by shaping the electrode-forming material. By shaping the electrode-forming material, the composite layer can be easily formed into a desired shape.

[0014] The present invention also aims to advantageously solve the above-mentioned problems, and the method for producing an electrochemical device of the present invention is characterized by comprising step (A) of producing at least one of a positive electrode and a negative electrode using a method for producing an electrode for an electrochemical device, and step (B) of contacting the electrode produced in step (A) with a separator containing an ion source. In this way, by contacting the electrode produced using the method for producing an electrode for an electrochemical device of the present invention with a separator containing an ion source, it is possible to supply ions to the composite layer of the electrode during the production of an electrochemical device, even if corrosion of the production equipment is suppressed when producing an electrode using an electrode forming material containing an ion conductor having an ion conductivity of a predetermined value or less.

[0015] Further, the present invention has an object to advantageously solve the above-mentioned problems, and the electrode forming material of the present invention is a material having an ionic conductivity of 10 at a temperature of 5° C. and an active material. -4 S / cm or less, the ion conductor includes a low molecular weight organic compound having a molecular weight of less than 10,000, and the low molecular weight organic compound is characterized in that the proportion of compounds having a volatility rate equal to or higher than that of N-methylpyrrolidone is 0% by mass or more and 20% by mass or less. In this way, by setting the ionic conductivity of the ion conductor to the above upper limit or less, corrosion of a manufacturing device can be suppressed when the ion conductor is used in the manufacture of an electrode. In addition, if the proportion of compounds having a volatility rate equal to or higher than that of N-methylpyrrolidone in the low molecular weight organic compound is 20% by mass or less, odor problems can be suppressed during the manufacture of an electrode.

[0016] Here, in the electrode forming material of the present invention, the ion conductor is preferably a viscous composition containing a polymer in a proportion of 50% by mass or less. If the content of the polymer in the ion conductor is 50% by mass or less, an electrode forming material that is easy to prepare and in which the content of the active material can be easily increased can be obtained.

[0017] In the electrode forming material of the present invention, it is preferable that the ion conductor does not contain an ionic substance. If the ion conductor does not contain an ionic substance, corrosion of the manufacturing equipment can be further suppressed. Effect of the Invention

[0018] According to the present invention, it is possible to provide a method for manufacturing an electrode for an electrochemical device which is less likely to cause problems of corrosion of the manufacturing equipment and odor generation, and a method for manufacturing an electrochemical device using an electrode manufactured by this method. Furthermore, according to the present invention, it is possible to provide an electrode molding material that can suppress the occurrence of problems of corrosion of manufacturing equipment and odor generation when used in the manufacture of electrodes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The method for producing an electrode for an electrochemical device of the present invention is not particularly limited, and can be used for producing electrodes for electrochemical devices such as primary batteries such as lithium primary batteries, non-aqueous secondary batteries such as lithium ion secondary batteries, lithium metal secondary batteries, sodium ion secondary batteries, potassium ion secondary batteries, magnesium secondary batteries, and aluminum secondary batteries, solar cells such as dye-sensitized solar cells, capacitors such as electric double layer capacitors and lithium ion capacitors, electrochromic display devices, electrochemical light-emitting elements, electric double layer transistors, and electrochemical actuators. In the method for producing an electrode for an electrochemical device of the present invention, an electrode is produced using the electrode molding material of the present invention. The method for producing an electrochemical device of the present invention is also used when producing an electrochemical device by using an electrode produced according to the method for producing an electrode for an electrochemical device of the present invention. The electrochemical device described above is preferably a non-aqueous secondary battery, and more preferably a lithium ion secondary battery.

[0020] (molding material for electrodes) The electrode forming material of the present invention is an active material having an ionic conductivity of 10 at a temperature of 5° C. -4 and an ion conductor having a molecular weight of less than 10,000. The ion conductor contains a low molecular weight organic compound having a molecular weight of less than 10,000, and may further contain a polymer. The electrode molding material may further contain at least one selected from the group consisting of a conductive filler, a fiber component, and an additive.

[0021] <Active material> The active material is not particularly limited, and any active material can be used depending on the type of electrochemical device. The active material contained in the electrode forming material may be composed of only one type of active material, or may be a mixture of two or more types of active materials.

[0022] Among them, it is preferable to use a nano-sized active material (maximum diameter less than 1 μm) as the active material, and it is more preferable to use an active material with a volume average particle diameter of 100 nm to 900 nm. If a nano-sized active material is used, the contact interface area with the ion conductor is increased, so that an electrode having excellent strength can be formed, and an electrode capable of smoothly progressing the electrochemical reaction can be formed. In the present invention, the volume average particle size of the active material can be measured in accordance with JIS K8825.

[0023] The content of the active material in the electrode forming material is preferably 50% by volume or more, more preferably 60% by volume or more. When the content of the active material is equal to or more than the lower limit, an electrode capable of producing a high-capacity electrochemical device can be formed.

[0024] <Ionic conductor> An ionic conductor is a material capable of transporting ions. The ionic conductor includes a low molecular weight organic compound having a molecular weight of less than 10,000, and optionally further includes a polymer. The ionic conductor has an ionic conductivity of 10 at a temperature of 5° C. -4 Thus, when the ionic conductivity at a temperature of 5° C. is equal to or less than the above upper limit, the content of salts and the like that may cause corrosion of the manufacturing equipment used in manufacturing the electrode can be sufficiently reduced, and the corrosion of the manufacturing equipment can be sufficiently suppressed. It is preferable that the ion conductor does not contain an ionic substance. If the ion conductor does not contain an ionic substance, it is possible to suppress corrosion of the manufacturing equipment used in manufacturing the electrode and to prevent the introduction of moisture due to moisture absorption. Furthermore, if the ion conductor does not contain an ionic substance, it is possible to determine the forming conditions of the electrode without being affected by the decomposition of the ionic substance.

[0025] [Low molecular weight organic compounds with molecular weights of less than 10,000] The low molecular weight organic compound having a molecular weight of less than 10,000 contains 80% by mass or more of compounds whose volatility is lower than that of N-methylpyrrolidone (hereinafter, may be referred to as "low volatility compounds"), and optionally contains 0% by mass or more and 20% by mass or less of compounds whose volatility is equal to or higher than that of N-methylpyrrolidone (hereinafter, may be referred to as "high volatility compounds"). If the proportion of the highly volatile compound in the low molecular weight organic compound is 20 mass % or less, the components that volatilize during the formation of the electrode can be reduced, and the occurrence of odor problems can be suppressed.

[0026] Here, the content of the low molecular weight organic compound in the ion conductor is usually 50% by mass or more, preferably 70% by mass or more, preferably 99% by mass or less, and more preferably 97% by mass or less. If the content of the low molecular weight organic compound is equal to or more than the above lower limit, the preparation of the electrode molding material becomes easy. Also, if the content of the low molecular weight organic compound is equal to or less than the above upper limit, the formation of an electrode using the electrode molding material becomes easy.

[0027] [Low volatility compounds] Here, examples of the low volatility compound include, but are not limited to, trisethylhexyl phosphate, adiponitrile, 1,3-propane sultone, glutaric anhydride, succinic anhydride, succinonitrile, tributyl phosphate, tetraglyme, diglycolic anhydride, sulfolane, ethyl methyl sulfone, dimethyl sulfone, trisbutoxyethyl phosphate, sulfolene, diethyl sulfone, ethylene sulfate (1,3,2-dioxathiolane-2,2-dioxide), vinyl ethylene carbonate, ethylene carbonate, N-methyloxazolidone, propylene carbonate, fluoroethylene carbonate, triglyme, triethyl phosphate, citraconic anhydride, methyl carbamate, and dimethylimidazolidinone. Among these, from the viewpoint of further reducing the components that volatilize during the formation of the electrode, trisethylhexyl phosphate, adiponitrile, 1,3-propane sultone, glutaric anhydride, succinic anhydride, succinonitrile, tributyl phosphate, tetraglyme, diglycolic anhydride, sulfolane, ethyl methyl sulfone, dimethyl sulfone, trisbutoxyethyl phosphate, sulfolene, diethyl sulfone, ethylene sulfate (1,3,2-dioxathiolane-2,2-dioxide), vinyl ethylene carbonate, ethylene carbonate, N-methyl oxazolidone, propylene carbonate, fluoroethylene carbonate, triglyme, etc. Preferred are organic compounds having a higher volatility than triethyl phosphate, and more preferred are organic compounds having a higher volatility than propylene carbonate, such as trisethylhexyl phosphate, adiponitrile, 1,3-propane sultone, glutaric anhydride, succinic anhydride, succinonitrile, tributyl phosphate, tetraglyme, diglycolic anhydride, sulfolane, ethyl methyl sulfone, dimethyl sulfone, trisbutoxyethyl phosphate, sulfolene, diethyl sulfone, ethylene sulfate (1,3,2-dioxathiolane-2,2-dioxide), vinyl ethylene carbonate, ethylene carbonate, and N-methyloxazolidone. The above-mentioned organic compounds may be used alone or in combination of two or more. Among them, from the viewpoint of reducing the components volatilized during the formation of the electrode and improving the solubility of the polymer, etc., it is preferable to use two or more of the above-mentioned organic compounds in combination as the low volatility compound, and more preferably to use three or more of them in combination.

[0028] The proportion of the low volatility compound in the low molecular weight organic compounds is not particularly limited as long as it is 80% by mass or more, but is preferably 90% by mass or more.

[0029] [Highly volatile compounds] Furthermore, the high volatility compound is not particularly limited, and examples thereof include N-methylpyrrolidone, γ-butyrolactone, dimethyl oxalate, vinylene carbonate, dimethyl sulfoxide, trimethyl phosphate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, ethyl propionate, and propyl propionate. Among these, from the viewpoint of reducing the amount of volatilization during electrode formation, organic compounds such as N-methylpyrrolidone, γ-butyrolactone, dimethyl oxalate, vinylene carbonate, dimethyl sulfoxide, and trimethyl phosphate, which have a volatility rate equal to or higher than that of trimethyl phosphate, are preferred. The above organic compounds may be used alone or in combination of two or more.

[0030] The proportion of the high volatility compound in the low molecular weight organic compounds is not particularly limited as long as it is from 0 mass % to 20 mass %, but is preferably 10 mass % or less.

[0031] The low molecular weight organic compound preferably has a content of 0% by mass or more and 20% by mass or less, more preferably 10% by mass or less, of a compound that is liquid under atmospheric pressure at a temperature of 5° C. If the content of the compound that is liquid under atmospheric pressure at a temperature of 5° C. is equal to or less than the above upper limit, it is possible to obtain an electrode molding material that is difficult to burn, and to prevent the volatilized compound from adhering to the surroundings as a liquid and causing mechanical failure, etc.

[0032] Here, examples of compounds that are liquid at a temperature of 5°C under atmospheric pressure include, but are not limited to, trisethylhexyl phosphate, adiponitrile, 1,3-propane sultone, tributyl phosphate, tetraglyme, trisbutoxyethyl phosphate, vinyl ethylene carbonate, propylene carbonate, triglyme, triethyl phosphate, citraconic anhydride, N-methylpyrrolidone, γ-butyrolactone, trimethyl phosphate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, ethyl propionate, and propyl propionate.

[0033] [polymer] The polymer, which is an optional component, is not particularly limited, and may be, for example, a polyether polymer, an acrylic polymer, a polyacrylonitrile polymer, a polyoxazoline polymer, or an aliphatic polycarbonate polymer. Specific examples of the polymer include polyethylene oxide, ethylene oxide copolymer, side-chain ethylene oxide polymer, hydrin rubber, polyvinyl acetate, vinyl chloride-vinyl acetate copolymer, polyoxazoline, side-chain oxazoline copolymer, polyacrylonitrile, nitrile rubber, acrylic acid ester copolymer, polymethyl methacrylate, styrene-acrylate copolymer, and acrylic rubber. These polymers may be used alone or in combination of two or more. The polymer preferably has a weight average molecular weight of 10,000 or more, more preferably 100,000 to 30,000,000, as measured in accordance with JIS K7252. The polymer does not include polymers that are polymerized in an electrochemical device.

[0034] Among them, the polymer is preferably a polymer that dissolves in the low molecular weight organic compound. Specifically, the polymer is preferably a polymer that increases the viscosity of the low molecular weight organic compound when added to the low molecular weight organic compound. In addition, when the low molecular weight organic compound is solid at room temperature, the presence or absence of an increase in viscosity can be confirmed by adding the polymer to the low molecular weight organic compound that has been heated to make it liquid.

[0035] In addition, the polymer preferably has a small gel content from the viewpoint of dissolving well in the ion conductor. The gel content is preferably 20 mass % or less of the polymer, more preferably 10 mass % or less, and even more preferably 5 mass % or less. The gel content of the polymer can be determined by adding the polymer to propylene carbonate in a ratio of 5 mass %, stirring and dissolving at 100°C for 12 hours, filtering the insoluble matter with a membrane filter at 100°C, vacuum drying to remove the propylene carbonate, and measuring the weight of the residue.

[0036] The content of the polymer in the ion conductor is preferably 1% by mass or more, more preferably 3% by mass or more, and preferably 50% by mass or less, and more preferably 30% by mass or less. By setting the content of the polymer to the above upper limit or less, the active material and the ion conductor can be mixed well even when the content of the active material in the obtained electrode forming material is increased to, for example, 70% by mass or more. Furthermore, by setting the content of the polymer to the above lower limit or more, it is possible to easily form an electrode using the electrode forming material. When the ionic conductor contains a polymer, the ionic conductor is preferably a composition having viscosity.

[0037] [Ionic substances] When an ionic substance is blended, any ionic substance can be used depending on the type of ions used in the electrochemical reaction in the electrochemical device. The ionic substance is preferably a substance that is compatible with low molecular weight organic compounds and polymers.

[0038] The ionic substance is preferably a substance that is resistant to moisture. The ionic substance is not particularly limited, and examples thereof include bis(fluorosulfonyl)imide anion, bis(trifluoromethanesulfonyl)imide anion, bis(oxalate)borate anion, difluorooxalateborate anion, ClO4 - , NO3 - , BF4 - , I - , I3 - Salts having the anion such as the above are preferred, and salts having the anion such as a bis(oxalate)borate anion or a difluorooxalateborate anion are more preferred. Specifically, when the electrochemical device is a lithium ion secondary battery or a lithium ion capacitor, the ionic substance may be a lithium salt of the above-mentioned anion, or when the electrochemical device is a magnesium secondary battery, the ionic substance may be a magnesium salt of the above-mentioned anion. These ionic substances may be used alone or in combination of two or more.

[0039] The content of the ionic substance in the ionic conductor is preferably, for example, 0.1 mass % or less.

[0040] [Properties of ionic conductors] The ionic conductor is not particularly limited, but preferably has the following properties.

[0041] 〔viscosity〕 The ionic conductor preferably has components that are compatible with each other, and is more preferably liquid under atmospheric pressure at a temperature of 35° C. The viscosity of the ionic conductor at a temperature of 25° C. is preferably 10 mPa s or more, more preferably 20 mPa s, and even more preferably 50 mPa s or more. In the present invention, the term "viscosity" refers to a viscosity measured at a temperature of 25°C using an EMS viscometer (Kyoto Electronics Manufacturing Co., Ltd., EMS-1000S) under sealed conditions at a motor speed of 1000 rpm so that the organic composition does not volatilize and moisture in the air does not get mixed in. The viscosity measured by this measurement method is basically the same as the value measured in accordance with JIS Z8803. The viscosity of the ionic conductor can be adjusted by changing the composition of the ionic conductor. Specifically, for example, the viscosity of the ionic conductor can be increased by blending a high-viscosity compound. Furthermore, when it is desired to know the composition that will become a liquid when solid compounds are mixed, equal amounts of all compounds used in the formulation of the composition are mixed, and the whole is heated to a temperature equal to or higher than the melting point of the compound with the highest melting point among those compounds until it is melted, and then cooled to the temperature at which it is desired to use it as a liquid. If the whole remains liquid, it can be used as is, but if some of it becomes solid, the composition of the supernatant can be quantified by gas chromatography or liquid chromatography to determine the composition that will become a liquid.

[0042] <Conductive filler> The conductive filler, which is an optional component, is not particularly limited, and any conductive filler that can be used in the field of electrochemical devices, particularly a particulate conductive filler, such as acetylene black, ketjen black, graphite, graphene, etc., can be used. By including the conductive filler, an electrode with excellent conductivity can be formed.

[0043] The content of the conductive filler in the electrode molding material is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and preferably 100 parts by mass or less, and more preferably 70 parts by mass or less, per 100 parts by mass of the ion conductor. If the content of the conductive filler is equal to or more than the lower limit, the conductivity of the electrode can be sufficiently increased. If the content of the conductive filler is equal to or less than the upper limit, it is possible to prevent the electrode molding material from being difficult to prepare due to the difficulty in mixing.

[0044] <Fiber components> The optional fiber component is not particularly limited, and it is preferable to use a fiber component with a nano-sized fiber diameter (maximum diameter less than 1 μm), and more preferably to use a fiber component with an average fiber diameter of 0.4 nm to 500 nm. If a fiber component with a nano-sized fiber diameter is blended, it helps the components contained in the electrode molding material to be cohesive, and an electrode with excellent strength can be formed. The fiber diameter can be measured using a microscope such as a scanning electron microscope or a transmission electron microscope. The fiber diameter before blending may be nano-sized, or may be nano-sized after being kneaded as an electrode molding material, but it is important that nano-sized bridges are formed between the particles of the active material. When observing the electrode with a microscope, it is preferable that there are 10 or more bridges in a field of view of 100 μm square, and more preferably 20 or more bridges. If a volatile organic compound is present and it is not suitable for observation, it is preferable to dry the electrode before observation.

[0045] Here, the fiber component having a nano-sized fiber diameter is not particularly limited, and examples thereof include carbon nanotubes, carbon nanofibers, cellulose nanofibers, and PTFE (polytetrafluoroethylene) nanofibers.

[0046] The amount of the fiber component is not particularly limited, and is preferably 8 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less, per 100 parts by mass of the active material. If the amount of the fiber component is equal to or less than the upper limit, a decrease in the electrode density can be suppressed.

[0047] <Additives> The optional additives are not particularly limited, and any additives that can be used in the field of electrochemical devices, such as electrode protectants and flame retardants, can be used. In addition, it is preferable to use an additive having a low volatility, it is more preferable to use a compound having a volatility lower than that of triethyl phosphate, and it is even more preferable to use a compound having a volatility lower than that of polycarbonate.

[0048] [Electrode protection agent] The electrode protecting agent is not particularly limited, and any electrode protecting agent that can be used in the field of electrochemical devices can be used. Specifically, examples of the negative electrode protecting agent include fluoroethylene carbonate, vinylene carbonate, 1,3,2-dioxathiolane-2,2-dioxide, 1,3-propane sultone, butane sultone, vinyl ethylene carbonate, and diallyl carbonate.

[0049] [Flame retardant] As the flame retardant, phosphates having 24 or less carbon atoms, phosphites having 24 or less carbon atoms, phosphazenes, etc. can be used. Among them, it is preferable to use phosphates as the flame retardant.

[0050] Further, as additives, whiskers, red phosphorus, aluminum hydroxide, magnesium hydroxide, antimony, cyclophosphazene oligomer, silica, alumina, zirconia, barium titanate, melamine, melamine cyanurate, ammonium carbonate, ammonium chloride, sodium bicarbonate, oxybisbenzylhydrazide, and the like can also be used. The content of each additive in the electrode forming material is not particularly limited, but is usually 5 mass % or less.

[0051] <Physical properties of electrode molding material> The electrode forming material is preferably in a clay-like or powder form, and more preferably in a clay-like form. In addition, the electrode molding material preferably has a porosity of 10% by volume or less, or a porosity that becomes 10% by volume or less when compressed. By using an electrode molding material having the above-mentioned porosity, a high-density electrode can be formed.

[0052] <Preparation of electrode molding material> The electrode forming material is not particularly limited, and can be prepared by mixing the above-mentioned components in any order. If the prepared electrode forming material is not to be used immediately, it is preferable to store it in a sealed container or with a protective film attached thereto to prevent the components contained therein from volatilizing off.

[0053] (Method of manufacturing electrodes for electrochemical devices) The method for producing an electrode for electrochemical devices of the present invention can be used to produce an electrode including a composite layer formed using the electrode molding material of the present invention. That is, the electrode produced according to the method for producing an electrode for electrochemical devices of the present invention may be composed of only the electrode molding material, or may have a composite layer formed using the electrode molding material on the surface of a current collector or the like. In this way, by using the electrode molding material of the present invention, an electrode having a high content of active material can be obtained while suppressing the occurrence of problems of corrosion and odor in the device. In the electrode produced by the production method of the present invention, a plurality of composite layers formed using the electrode-forming material may be laminated. The plurality of electrode-forming materials to be laminated may have different compositions.

[0054] <Electrode> Specifically, the electrode may be, for example, an electrode formed by forming the electrode forming material of the present invention into an arbitrary shape such as a sheet, or may be formed by attaching the electrode forming material to a current collector. Here, the electrode may have a uniform thickness or a gradient in thickness. An electrode with a gradient in thickness can be manufactured, for example, by nipping with rolls having different clearances at both ends. Since the electrodes maintain their bond only through physical affinity, if they are in a sheet form that can easily conform to the shape of the adherend, such as a current collector, they can easily maintain close contact with the adherend.

[0055] Here, when the electrode-forming material is attached to the current collector, the shape of the electrode-forming material to be attached may be any shape. In addition, the electrode-forming material may be attached to only one side of the current collector, or may be attached to both sides of the current collector.

[0056] Furthermore, the collector preferably has a through hole at the portion where the electrode molding material is attached. If the collector has a through hole at the portion where the electrode molding material is attached, the electrode molding material can be filled into the through hole, and the electrode molding material can be attached well. Also, if the collector has a through hole, for example, when an active material having an initial irreversible capacity is used as the active material, pre-doping can be easily performed using the vertical pre-doping method.

[0057] In addition, the collector preferably has a conductive coating on the surface that contacts the electrode molding material. If the collector has a conductive coating on the surface that contacts the electrode molding material, the conductivity of the electrode can be increased, and the unevenness of the surface can increase the adhesion to the electrode molding material. The conductive coating is not particularly limited, and any conductive coating that can be used in the field of electrochemical devices can be used.

[0058] The composite layer formed using the electrode molding material must have a porosity of 10% by volume or less, and preferably 5% by volume or less. If the porosity of the portion formed using the electrode molding material is equal to or less than the upper limit, the electrochemical reaction can be smoothly promoted in the electrochemical device. In addition, ions can be smoothly supplied into the electrode during the manufacture of the electrochemical device.

[0059] In addition, in the composite layer formed using the electrode molding material, the electrode molding material is preferably crosslinked or polymerized, because if the electrode molding material is crosslinked or polymerized, an electrode with high strength can be obtained. The method for crosslinking or polymerizing the electrode forming material is not particularly limited, and known methods such as heating and irradiation with ultraviolet rays or electron beams can be used.

[0060] <Formation of composite layer> The formation of the composite layer using the electrode molding material is not particularly limited, and can be performed by molding the electrode molding material in an open atmosphere. Here, the "open atmosphere" refers to an atmosphere in which the electrode molding material is in contact with the atmosphere, such as an atmosphere in which an air current is present or an atmosphere under vacuum, and is not saturated with vapor from the electrode molding material. In addition, the composite layer is preferably formed at a temperature equal to or higher than the dew point of the manufacturing atmosphere in order to prevent adhesion of moisture. For the same reason, it is preferable not to use a processing machine that uses water as a coolant (or heat medium) in forming the composite layer.

[0061] Furthermore, the manufacturing method of the present invention uses an electrode molding material having a low proportion of compounds whose volatility is equal to or greater than that of N-methylpyrrolidone. Therefore, unlike manufacturing methods using slurries containing large amounts of solvent, a composite layer can be formed without a drying step for drying the electrode molding material.

[0062] When manufacturing an electrode composed only of an electrode molding material, the electrode molding material can be molded into a desired shape, such as a sheet, without any particular limitation, and then optionally crosslinked or polymerized to manufacture an electrode composed of a composite layer. In addition, when forming the electrode forming material into a sheet, it is preferable to crush a plurality of strands of the electrode forming material to form the sheet, without any particular limitation, from the viewpoint of easily obtaining a sheet made of the electrode forming material and making the sheet thinner. Here, the cross-sectional shape of the strands may be a circle, an ellipse, a triangle, a square, or other polygon. From the viewpoint of not generating pores in the electrode, shapes that do not have depressions, such as a star shape, are preferable.

[0063] In addition, when manufacturing an electrode by attaching an electrode molding material to the surface of a current collector, the electrode molding material can be shaped into a desired shape and then attached to one or both sides of the current collector to manufacture an electrode having a composite layer on the current collector, without any particular limitation. If the electrode molding material is shaped and then attached, the composite layer made of the electrode molding material provided on the current collector can be easily shaped into a desired shape. Here, when shaping is performed after attachment to the current collector, or when attaching and shaping are performed simultaneously, it is preferable to limit the force applied or the content of the work so as not to deform or damage the current collector. When the electrode-forming material is applied to both sides of the current collector, it is preferable that the electrode-forming material is applied to both sides of the current collector at approximately the same time, and more preferably at the same time.

[0064] When the electrode is produced as described above, it is preferable to include a step of adjusting the shape and / or thickness of the composite layer.

[0065] The shape of the composite layer can be easily adjusted, for example, by scraping off the electrode molding material.

[0066] The thickness of the composite layer can be easily adjusted, for example, by crushing the electrode-forming material with a roll or the like, or by scraping off the electrode-forming material.

[0067] Here, when the thickness is adjusted by squeezing the electrode forming material, it is preferable to squeeze the electrode forming material on a curved surface with a radius of curvature of 100 mm or less from the viewpoint of easily adjusting the thickness. In addition, when squeezing, squeezing while controlling the clearance to a constant value makes it easier to obtain an electrode with a uniform thickness. In addition, the curved surface with a radius of curvature of 100 mm or less is preferably in the shape of a roll, and more preferably rotated. The rotation may be at the same speed as the electrode forming material, or may have a speed difference in the forward or reverse direction. By providing a speed difference, it is possible to control which side the electrode forming material sticks to. When sandwiched between objects with different speeds, in many cases, the electrode forming material is more likely to stick to the object with the faster speed. It is preferable to perform the squeezing process in two or more stages to gradually reduce the thickness rather than in one stage, since this reduces the stress on the electrode forming material. In addition, when controlling the thickness accuracy of the electrode molding material to a high accuracy of, for example, within ±5%, it is preferable to roughly adjust the thickness and then fine-adjust it with a curved surface having a curvature radius of 0.5 mm or more. The thickness accuracy of the electrode can be improved by smoothing the electrode molding material with a curved surface having a curvature radius of 0.5 mm or more. In this case, it may be the curved surface or the electrode molding material that is moving, or both of them may be moved. It is preferable to smooth with a constant pressure, and the pressure is preferably strong enough not to change the average thickness of the electrode by 1% or more.

[0068] In addition, when a roll is used to crush the electrode forming material, the surface of the roll is preferably non-adhesive, and more preferably made of ceramic, fluorine-based polymer or silicone-based polymer, or metal. The roll surface may be treated to increase the surface roughness, such as by making it matte. The surface roughening treatment can be performed by sandblasting or the like. If the surface is roughened too much, the electrode forming material may be buried in the holes (concave portions), so the height difference of the roughness is preferably 20 μm or less, and the major axis of the holes is preferably 20 μm or less. In addition, a tape of a constant thickness may be attached to the surface of the roll to control the thickness. Furthermore, a pattern may be applied to the surface of the roll and the pattern may be transferred to the electrode forming material. In addition, from the viewpoint of suppressing the volatilization of components from the electrode forming material, it is preferable that the roll has a small diameter. Furthermore, from the viewpoint of preventing the electrode forming material from sticking to the roll, it is preferable that the surface of the electrode forming material that comes into contact with the roll is corrugated or unevenly formed by, for example, a method such as shaping or notching. The height difference of the corrugation or unevenness is preferably 1 to 95% of the thickness of the thickest part of the electrode forming material. The shaping can be carried out by forming the shape of the outlet die of the kneader into a corrugated shape, etc. Also, by imparting such a shape to the surface of the electrode-forming material, the electrode-forming material becomes more easily crushed, making it easier to control the thickness.

[0069] In the electrode manufacturing method of the present invention, it is preferable to measure the thickness of the electrode molding material and feedback-control the basis weight of the electrode molding material. The electrode molding material has a ratio of compounds with a volatility rate equal to or higher than that of N-methylpyrrolidone of 0% by mass to 20% by mass, and the basis weight can be easily determined from the thickness. If the thickness is measured and the basis weight is feedback-controlled, the basis weight can be easily controlled. The thickness can be easily measured using a contact thickness gauge or a laser thickness gauge.

[0070] The electrode manufactured according to the manufacturing method of the present invention has an ionic conductivity of 10 -4These are formed using an electrode molding material containing an ionic conductor with an ionic conductivity of 0.1 S / cm or less, and usually cannot be used as is to operate an electrochemical device. Therefore, when used in an electrochemical device, the composite layer is somehow supplemented with the amount of ionic substance required to operate the electrochemical device. It is preferable that the electrode produced according to the production method of the present invention is incorporated into the electrochemical device as soon as possible after production, and the electrode is preferably incorporated within 20 days, more preferably within 10 days, and even more preferably within 5 days.

[0071] (Method of manufacturing electrochemical devices) The method for manufacturing an electrochemical device of the present invention is used when manufacturing an electrochemical device using an electrode manufactured using the method for manufacturing an electrode for an electrochemical device of the present invention, and even when an electrode manufactured using the manufacturing method of the present invention is used, it is possible to provide an electrochemical device that operates well by replenishing ions in the composite layer of the electrode. The method for producing an electrochemical device of the present invention includes step (A) of producing at least one of a positive electrode and a negative electrode using the method for producing an electrode for an electrochemical device of the present invention, and step (B) of contacting the electrode produced in step (A) with a separator containing an ion source. In this way, by contacting the electrode with the separator containing the ion source in step (B), ions can be replenished in the composite layer of the electrode, and therefore an electrochemical device that operates well can be provided.

[0072] <Process (A)> Here, in the step (A), at least one of a positive electrode and a negative electrode is produced using the method for producing an electrode for electrochemical devices of the present invention.

[0073] <Process (B)> In step (B), the electrode produced in step (A) is brought into contact with a separator containing an ion source, for example, in an exterior material, and ions are replenished from the ion source to the composite layer of the electrode. Then, an electrochemical device is obtained that includes a positive electrode, a negative electrode, a separator, and optionally further contains an electrolyte solution. Note that the composite layer of the electrode produced in step (A) has a porosity of 10 volume % or less, so that ions can be replenished well.

[0074] Here, when only one of the positive electrode and the negative electrode is manufactured using the manufacturing method of the electrode for electrochemical devices of the present invention in step (A), any counter electrode such as a metal electrode can be used as the counter electrode. In particular, it is preferable to use an electrode made of at least one selected from an alkali metal, an alkaline earth metal, and metallic aluminum as the counter electrode. Although the manufacturing method of the present invention allows the electrode to be manufactured in an open atmosphere, there is a risk that the electrode manufactured in an open atmosphere will contain more moisture than conventional electrodes. However, if the above-mentioned counter electrode is used, the moisture brought in from the electrode can be captured well.

[0075] The separator containing an ion source is not particularly limited, and a separator having an ion source such as an ionic substance can be used. The ionic substance is not particularly limited, and the same ionic substances as those exemplified as those that can be contained in the electrode forming material of the present invention can be used. The amount of the ion source to be contained can be determined from the salt concentration required to operate the electrochemical device.

[0076] Furthermore, the electrolyte is not particularly limited, and any electrolyte used in electrochemical devices can be used.

[0077] In addition, in the electrochemical device manufactured according to the manufacturing method of the present invention, at least one of the counter electrode and the separator preferably contains an inorganic filler having a moisture trapping ability and / or an ionic substance having a moisture trapping ability. If the counter electrode or the separator contains an inorganic filler having a moisture trapping ability and / or an ionic substance having a moisture trapping ability, the moisture brought in from the electrode can be well trapped. The inorganic filler having a moisture trapping ability is not particularly limited, and for example, silica, alumina, magnesium sulfate, calcium sulfate, magnesium oxide, calcium oxide, magnesium hydride, lithium hydride, calcium hydride, or phosphorus pentoxide particles can be used. The ionic substance having a moisture trapping ability is not particularly limited, and for example, bis(oxalate)borate salt, difluorooxalate borate salt, etc. can be used. EXAMPLES

[0078] First, the following Reference Example 1 was carried out to evaluate the volatility of each compound.

[0079] (Reference example 1) In a dry room controlled at a room temperature of 18°C ​​and a dew point of -40°C or less, 1g of each of the organic compounds shown in Table 1 was weighed out onto an aluminum dish with a diameter of 5cm and placed, without a lid, in a draft chamber controlled at a wind speed of 0.5m / min. After 12 hours, the weight was measured and the volatilization rate (= (reduced mass / initial mass) x 100%) was evaluated. The results are shown in Table 1.

[0080] [Table 1]

[0081] Next, the following examples and comparative examples were carried out. The following operations were carried out in a dry room controlled at a dew point of -40°C or less.

[0082] Example 1 <Production of negative electrodes> A twin-screw extruder (L / D=30) with a kneading section and a vent section and a T-die that can be discharged in sheet form was used to feed 6 ethylene carbonate, 2 dimethyl sulfone, 1 ethylene oxide-propylene oxide copolymer with a molecular weight of 1 million, 1 PTFE nanofiber as a fiber component, and 50 graphite as a negative electrode active material, in a weight ratio of each, using a total of 6 screw-type quantitative feeders, and twin-screw kneading and sheeting were performed at room temperature of 25 ° C. The clearance at the die outlet was 100 μm, and the sheet was nipped with a roll of 200 mm diameter while being sandwiched from both sides with copper foil of 25 μm thickness as a current collector, and a sheet-shaped negative electrode with a thickness of 100 μm and a thickness accuracy of ± 3% was continuously obtained. The product temperature during this manufacturing process was 25 ° C, the same as room temperature, at the inlet of the extruder, 50 ° C due to the frictional heat caused by kneading in the sealed kneading section, and 25 ° C, the same as room temperature, at the outlet. Since the amount of volatile matter emitted from the materials was not completely zero, local exhaust ventilation equipment was installed and operated appropriately from the perspective of worker health. The negative electrode sandwiched between the copper foils thus produced was used as a test piece for measuring the interface resistance. The change in interface resistance after production is shown in Table 2. In the following, an impedance analyzer manufactured by Solartron was used to measure the interface resistance. No increase in resistance after production was observed. The porosity of the composite layer calculated from the electrode density was 0%. In addition, the ionic conductivity of the ionic conductor (composition: 6 parts ethylene carbonate, 2 parts dimethyl sulfone, and 1 part ethylene oxide-propylene oxide copolymer with a molecular weight of 1 million) used in the manufacture of the negative electrode was measured separately at a temperature of 5°C, and was found to be 10 -7 It was found that the density was less than S / cm. <Production of positive electrodes> A total of six screw-type quantitative feeders were used to feed the materials, in weight ratios, of ethylene carbonate 6, dimethyl sulfone 2, ethylene oxide-propylene oxide copolymer with a molecular weight of 1 million 1, PTFE nanofiber as a fiber component, lithium cobalt oxide 100 as a positive electrode active material, and acetylene black 3, into a twin-screw extruder of the same type as that used for the production of the negative electrode, and the materials were kneaded in a twin-screw and sheeted at room temperature of 25 ° C. The clearance at the die outlet was 100 μm, and the material was sandwiched on both sides with aluminum foil with a thickness of 25 μm as a current collector and nipped with a roll with a diameter of 200 mm to continuously obtain a sheet-shaped positive electrode with a thickness of 100 μm and a thickness accuracy of ± 3%. The product temperature during this manufacturing process was 25 ° C, the same as room temperature, at the inlet of the extruder, 50 ° C due to the frictional heat caused by kneading in the sealed kneading section, and 25 ° C, the same as room temperature, at the outlet. Since the amount of volatile matter emitted from the materials was not completely zero, local exhaust ventilation equipment was installed and operated appropriately from the perspective of worker health. The produced positive electrode sandwiched between aluminum foils was used as a test piece for measuring the interface resistance. The change in interface resistance after production is shown in Table 2. No increase in resistance after production was observed. The porosity of the composite layer calculated from the electrode density was 0%. In addition, the ionic conductivity of the ionic conductor (composition: 6 parts ethylene carbonate, 2 parts dimethyl sulfone, and 1 part ethylene oxide-propylene oxide copolymer with a molecular weight of 1 million) used in the manufacture of the positive electrode was measured separately at a temperature of 5°C, and was found to be 10 -7 It was found that the density was less than S / cm.

[0083] Comparative Example 1 <Production of negative electrodes> A twin-screw extruder (L / D=30) with a kneading section and a vent section and a T-die that can be discharged in sheet form was used to feed ethylene carbonate 5, dimethyl sulfone 2, ethylene oxide-propylene oxide copolymer with a molecular weight of 1 million 1, PTFE nanofiber as a fiber component 0.5, lithium bis(fluorosulfonyl)imide as an ionic material 1, and graphite (604A, manufactured by Nippon Carbon Co., Ltd.) as a negative electrode active material in a weight ratio of 50, using a total of six screw-type quantitative feeders, and twin-screw kneading and sheeting were performed at room temperature of 25 ° C. The clearance at the die outlet was set to 100 μm, and the material was sandwiched from both sides with copper foil with a thickness of 25 μm as a current collector and nipped with a roll with a diameter of 200 mm to continuously obtain a sheet-shaped negative electrode with a thickness of 100 μm and a thickness accuracy of ± 3%. The manufactured negative electrode sandwiched between copper foils was used as a test piece for measuring the interface resistance. The change in interface resistance after manufacturing is shown in Table 2. There was a tendency for the resistance to increase after manufacturing, which was thought to be due to corrosion of the current collecting foil by salt (ionic substance). <Production of positive electrodes> A total of seven screw-type quantitative feeders were used to feed the materials, each in a weight ratio of 5 ethylene carbonate, 2 dimethyl sulfone, 1 million molecular weight ethylene oxide-propylene oxide copolymer, 1 PTFE nanofiber as a fiber component, 1 lithium bis(fluorosulfonyl)imide as an ionic material, 100 lithium cobalt oxide (Nippon Chemical Industry Co., Ltd., Cellseed C) as a positive electrode active material, and 3 acetylene black, into a twin-screw extruder. The materials were kneaded and sheeted at room temperature of 25 ° C. The clearance at the die outlet was set to 100 μm, and the material was sandwiched on both sides with 25 μm thick aluminum foil as a current collector and nipped with a roll of 200 mm in diameter to continuously obtain a sheet-shaped positive electrode with a thickness of 100 μm and a thickness accuracy of ± 3%. The produced positive electrode sandwiched between aluminum foils was used as a test piece for measuring the interface resistance. The change in interface resistance after production is shown in Table 2. There was a tendency for the resistance to increase after production, which was thought to be due to corrosion of the current collecting foil by salt (ionic substance).

[0084] [Table 2]

[0085] Example 2 Positive and negative electrodes were produced for one year according to Example 1. The devices were then moved to a warehouse in a normal temperature and humidity environment and left there for half a year, but no rust was observed.

[0086] Comparative Example 2 Positive and negative electrodes were manufactured for one year according to Comparative Example 1. After that, the device was taken out of the dry room and moved to a warehouse in a normal temperature and humidity environment. When the device was checked about half a year later, rust had formed on many of the metal parts of the device.

[0087] Example 3 3g of ethylene carbonate, 3g of propylene carbonate, 1g of ethylene oxide-propylene oxide-allyl glycidyl ether random copolymer (molar ratio 90:5:5) with a molecular weight of 1 million, 3g of LiBF4 as an ionic substance, 0.5g of magnesium oxide (Kyowamag (registered trademark) 30, manufactured by Kyowa Chemical Industry Co., Ltd.) as a filler having a moisture trapping ability, and 50mg of Irg651 as a UV crosslinking agent were weighed out and mixed at room temperature to obtain a uniform electrolyte composition. This was kneaded in an open mortar, sandwiched between two sheets of releasable PET film, and irradiated with UV to produce a crosslinked separator with a thickness of 100 μm. In addition, a positive electrode and a negative electrode were prepared in the same manner as in Example 1, except that the current collector was provided on only one side, and the separator was sandwiched between them to form a lithium ion battery. When the resistance of the separator of this battery was measured with a tester to evaluate the insulation performance, it was found to be 50 MΩ or more. The voltage was also measured, but it was 0 V. It is believed that the electrode produced according to the production method of the present invention does not contain an ionic substance as a supporting electrolyte necessary for the electrochemical reaction, so that no electrochemical reaction occurs in the electrode, and the insulation resistance could be measured immediately after production. Furthermore, when the battery was stored at 25°C for about three days and the voltage was measured, a voltage of about 100mV was generated. When it was then placed in a charge-discharge tester, it was able to be repeatedly charged and discharged between 4.2V and 3V. This is thought to be because ionic substances had diffused from the separator to the electrodes, making the electrodes capable of generating an electrochemical reaction. Once this state was reached, it was no longer possible to measure the insulation resistance.

[0088] Example 4 The same electrodes as in Example 3 were prepared, and a battery was manufactured using Celgard 2325 as a separator. The insulation resistance was measured in this state and found to be 50 MΩ or more. After that, an ethylene carbonate / diethyl carbonate (50 / 50) solution containing 1 M LiPF6 was poured into the battery, and after 3 days, it was placed in a charge / discharge tester and could be repeatedly charged and discharged between 4.2 V and 3 V.

[0089] Comparative Example 3 A separator was produced in the same manner as in Example 3. A positive electrode and a negative electrode were prepared in the same manner as in Comparative Example 1, except that the current collecting foil was placed on only one side, and the separator was sandwiched between them to form a lithium ion battery. When the resistance of the separator of this battery was measured with a tester to evaluate the insulation performance of the battery, the current from the battery flowed into the tester, making it impossible to measure the resistance.

[0090] Example 5 A negative electrode was produced in the same manner as in Example 3, except that 6 parts of ethylene carbonate and 2 parts of dimethyl sulfone were replaced with 8 parts of ethylene carbonate and 2 parts of dimethyl carbonate. During work, there was a strong odor of dimethyl carbonate, making the working environment inappropriate. Although the electrode was completed, its density was lower than the design. This is thought to be due to the evaporation of dimethyl carbonate, which resulted in the formation of pores. The porosity calculated from the electrode density was 4.5 vol.%. A positive electrode was also produced in the same manner, and a battery was produced in the same manner as in Example 3. The insulation resistance was measured, and it was 50 MΩ or more. The voltage was also measured, but it was 0 V. This battery was stored at 25°C for about 3 days and then put into a charge / discharge tester, and it was able to be repeatedly charged and discharged between 4.2 V and 3 V, as in Example 3.

[0091] Comparative Example 4 A negative electrode was produced in the same manner as in Example 4, except that 8 parts of ethylene carbonate and 2 parts of dimethyl carbonate were changed to 3 parts of ethylene carbonate and 7 parts of dimethyl carbonate. During work, there was a strong odor of dimethyl carbonate, making the working environment inappropriate. Although the electrode was completed, its density was lower than the design. This is thought to be due to the evaporation of dimethyl carbonate, which resulted in the formation of pores. The porosity calculated from the electrode density was 13 vol.%. A positive electrode was also produced in the same manner, and a battery was produced in the same manner as in Example 3. The insulation resistance was measured, and was 50 MΩ or more. The voltage was also measured, but it was 0 V. This battery was stored at 25°C for about 3 days and placed in a charge / discharge tester, but it reached 4.2 V immediately after the start of charging and could not be charged satisfactorily. It is believed that the large porosity caused insufficient diffusion of ions from the separator to the electrode. [Industrial Applicability]

[0092] According to the present invention, it is possible to provide a method for manufacturing an electrode for an electrochemical device which is less likely to cause problems of corrosion of the manufacturing equipment and odor generation, and a method for manufacturing an electrochemical device using an electrode manufactured by this method. Furthermore, according to the present invention, it is possible to provide an electrode molding material that can suppress the occurrence of problems of corrosion of manufacturing equipment and odor generation when used in the manufacture of electrodes.

Claims

1. The active material and the ionic conductivity at a temperature of 5° C. are 10 -4 and an ion conductor having a porosity of 10 volume % or less by molding an electrode molding material containing the electrode molding material and an ion conductor having a porosity of 10 volume % or less, The ionic conductor comprises a low molecular weight organic compound having a molecular weight of less than 10,000; The low molecular weight organic compound has a ratio of compounds having a volatility rate equal to or higher than that of N-methylpyrrolidone of 0% by mass or more and 20% by mass or less, The content of the ionic substance in the ionic conductor is 0.1 mass% or less, The volatilization rate is a value calculated by weighing out 1 g of the compound to be measured onto an aluminum dish having a diameter of 5 cm in a dry room controlled at a room temperature of 18° C. and a dew point of −40° C. or lower, placing the dish without a lid in a fume hood controlled at a wind speed of 0.5 m / min, and measuring the weight after 12 hours using the formula: (reduced mass / initial mass)×100%, in a method for manufacturing an electrode for electrochemical device.

2. 2 . The method for producing an electrode for an electrochemical device according to claim 1 , wherein the ionic conductor is a viscous composition containing a polymer in a proportion of 50% by mass or less.

3. The method for producing an electrode for an electrochemical device according to claim 1 or 2, wherein the ion conductor does not contain an ionic substance.

4. 4. The method for producing an electrode for an electrochemical device according to claim 1, wherein in the step, the electrode forming material is shaped to form the composite layer.

5. A step (A) of producing at least one of a positive electrode and a negative electrode by using the method for producing an electrode for electrochemical devices according to any one of claims 1 to 4; (B) contacting the electrode produced in the step (A) with a separator containing an ion source; A method for producing an electrochemical device, comprising:

6. An electrode molding material which is molded to form an electrode, The active material and the ionic conductivity at a temperature of 5° C. are 10 -4 and an ion conductor having a viscosity of 0.05 S / cm or less, The ionic conductor comprises a low molecular weight organic compound having a molecular weight of less than 10,000; The low molecular weight organic compound has a ratio of compounds having a volatility rate equal to or higher than that of N-methylpyrrolidone of 0% by mass or more and 20% by mass or less, The content of the ionic substance in the ionic conductor is 0.1 mass% or less, The volatilization rate is a value calculated by weighing out 1 g of the compound to be measured into an aluminum dish having a diameter of 5 cm in a dry room controlled at a room temperature of 18° C. and a dew point of −40° C. or less, placing the dish without a lid in a draft chamber controlled at a wind speed of 0.5 m / min, and measuring the weight after 12 hours using the formula: (reduced mass / initial mass)×100%.

7. The electrode molding material according to claim 6 , wherein the ion conductor is a viscous composition containing a polymer in a proportion of 50% by mass or less.

8. The electrode forming material according to claim 6 or 7, wherein the ion conductor does not contain an ionic substance.

Citation Information

Patent Citations

  • Radiation-curable solid electrolyte and equipment for electrolysis by using it

    JP1990000602A

  • Novel solid polymer electrolyte

    JP1992506983A

  • Cathode film for alkali metal polymer battery and manufacturing method thereof

    JP2005519442A

  • Manufacturing method of composite material for electrode

    JP2006522441A

  • Cathode for polymer electrolyte secondary battery and battery using the same

    JP2007323872A